PRODUCTION OF AMYLOLYTIC ENZYME BY RUMEN FUNGI, NEOCALLIMASTIX SP. K7 AND ORPINOMYCES SP. K5 - B. M. Kelleci; U. Comlekcioglu (Journal of Animal and Plant Sciences, 2016)
Neocallimastix sp. K7 and Orpinomyces sp. K5 were studied for their amylase production capability in starch, maltose, and glucose-containing cultures. The highest level of amylase was produced in 4 and 5 mg ml-1 starch-containing mediums of Orpinomyces sp. K5 and Neocallimastix sp. K7, respectively. Amylase production highly reduced in glucose-grown cultures of Orpinomyces sp. K5, whereas glucose stimulated the amylase production of Neocallimastix sp. K7 as effective as maltose. Both enzymes were optimally active at pH 5.5 and 45 °C. The pH stability range was 5.0 to 6.5 and inactivation occurred at 55 °C after 15 min for both enzymes. The highest amylase adsorption to starch was found at pH 5.5 and 6.5 in Orpinomyces sp. K5 and Neocallimastix sp. K7, respectively. The enzyme activities were inhibited in the presence of Cu2+, Zn2+ and Hg2+, while their activities were significantly stimulated by Mg2+ and Mn2+. Two amylase active bands were observed around 67 kDa. Glucose was determined as the only product of amylase action in Orpinomyces sp. K5. Glucose was the major product but maltose, maltotriose and maltotetraose were also detected in the enzymatic reaction of Neocallimastix sp. K7.
Keywords: Neocallimastix sp.; Orpinomyces sp.; starch; amylase